Pengaruh Motivasi, Model Komunikasi dan Stres Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Karyawan Gen Z Café Sarijan di Kota Malang) - Prastuti, Mashita Putri; Pardiman, Pardiman; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of motivation, communication models and work stress on employee job satisfaction (study of Gen z Café Sarijan employees in Malang City). This research method uses quantitative methods. The population used was generation z employees at the Sarijan café in Malang city and 90 respondents were obtained using purposive sampling techniques with criteria determined by the researcher. Data collection methods use online and offline questionnaires. The data analysis technique used is multiple linear regression analysis with the IBM SPSS Statictic 27 program. The research results show that Motivation, Communication Model and Job Stress simultaneously influence employee job satisfaction. Motivation partially has a positive and significant effect on employee job satisfaction, Communication Model partially has a positive and significant effect on employee job satisfaction, Job Stress partially has a positive and significant effect on employee job satisfaction. Keywords: Job Satisfaction, Motivation, Communication Model, Job Stress